2002
DOI: 10.1111/j.1750-3639.2002.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Caspase‐cleaved Amyloid Precursor Protein in Alzheimer's Disease

Abstract: Caspase-3 mediated cleavage of the amyloid precursor protein (APP) has been proposed as a putative mechanism underlying amyloidosis and neuronal cell death in Alzheimer's disease (AD). We utilized an antibody that selectively recognizes the neo epitope generated by caspase-3 mediated cleavage of APP (␣⌬C csp -APP) to determine if this proteolytic event occurs in senile plaques in the inferior frontal gyrus and superior temporal gyrus of autopsied AD and age-matched control brains. Consistent with a role for ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
31
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 46 publications
(83 reference statements)
11
31
0
Order By: Relevance
“…Previous immunohistochemical studies have shown immunoreactivity of active caspase-3 and caspase-3-cleaved substrates in neurons, senile plaques, and neurofibrillary tangles in AD, 17,18,38,39,[57][58][59][60] although not all investigators have reported these findings. 61 Of note is that none of these previous studies have focused on caspase-3 in synaptic terminal fields or neuropil.…”
Section: Discussionmentioning
confidence: 78%
“…Previous immunohistochemical studies have shown immunoreactivity of active caspase-3 and caspase-3-cleaved substrates in neurons, senile plaques, and neurofibrillary tangles in AD, 17,18,38,39,[57][58][59][60] although not all investigators have reported these findings. 61 Of note is that none of these previous studies have focused on caspase-3 in synaptic terminal fields or neuropil.…”
Section: Discussionmentioning
confidence: 78%
“…Caspase activation was involved in apoptosis (Cohen, 1997;Ayala-Groeso et al 2002;Amano et al 2005;Denecker et al 2008;Pop and Salvesen 2009;Hyman andYuan 2012, 2012). The two classical apoptotic pathways are the intrinsic, or mitochondrial pathway, and the extrinsic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies found that the cysteine-aspartic protease (caspase) family is involved in apoptosis (Ayala-Groeso et al 2002;Hyman and Yuan 2012). There are 15 different caspases known in mammals and 11 in humans (Pop and Salvesen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with Q3G prior to the oxidative insult significantly decreased the number of TUNEL-positive cells. To further evaluate the mechanism of cell death induced by H 2 O 2 , Western blot analysis was carried out using an antibody that detects caspase-3-cleaved spectrin (36). In SH-SY5Y cells treated with H 2 O 2 , higher levels of caspase-3-cleaved spectrin were detected compared with untreated cells (data not shown).…”
Section: Q3g But Not Quercetin Dihydrate Protected Sh-sy5y Hek293 Amentioning
confidence: 99%